Evaluation of the Pacific Financial Technical Assistance Centre. (Policy Papers; Policy Paper ;, 2004)
This report presents the analysis, findings, conclusions and recommendations of the evaluation of the Pacific Financial Technical Assistance Center (PFTAC) that was undertaken between April 26 and May 14, 2004.